(untitled) (ResearchJet Journal of Analysis and Inventions, 2023)
The prototype of the state educational standard for higher legal education was previously the so-called qualification characteristics. They set out the requirements for a law school graduate: what he should know, be able to do, what requirements of legal activity he should meet. Let us turn to the characteristics of the state standard of higher legal education, which operates in our country. It contains requirements for the minimum content and level of training of a graduate in the specialty “Jurisprudence”.